MANAGEMENT IN THE QUR'AN PERSPECTIVE - Sebad Linaci, Ahmad Novta; Patimah, Hj. Siti (Riviera Publishing, 2023)
Humans have targets or goals that they can achieve in their lives. To achieve targets or goals, human effort is required in the form of tips or methods that must be implemented or mastered. To be more systematic and focused in determining tips or techniques to achieve targets or goals required by management. Even though management as science itself was only known in the mid-19th century, its existence is the key to success in achieving a target or goal. The method used in this research is a library or library research approach. They are supported by descriptive concept analysis. Islamic teachings in the Al-Qur'an and the Prophet's hadith teach about a directed and orderly life. Al-Qur'an, with all its integral parts, also functions as a source for determining things, responding to them, and enlightening oneself about all actions taken. The management theories and concepts used today are familiar from an Islamic perspective. Management existed when Allah created the universe and its contents. Management is a process of skill and expertise in Planning, Organizing, directing, and supervising each person's efforts to achieve predetermined goals. There are at least four functions in management: Planning, Organizing, actualizing, and controlling. The Koran and Hadith are references and views of life in Muslim life, such as management.